Temporal-spatial variations in the elemental and stable isotope contents of eelgrass (Zostera marina L.) in the Bohai Sea and Yellow Sea, northern China: Sheath as a novel ecological indicator for geochemical research - Shaochun Xu (Elsevier, 2021)
Seagrasses play an important role in the geochemical cycling of elements in coastal ecosystems. Eelgrass (Zostera marina L.) is a marine foundation species essential for coastal ecosystem services in the temperate northern hemisphere. The elemental (C, N, and P) and isotope (δ13C and δ15N) contents of eelgrass tissues were measured at nine sampling sites across northern China. Trends at temporal and spatial scales were analyzed to examine temporal-spatial variations in seagrass characteristics, and relationships between different tissues were also analyzed to identify a valuable ecological indicator. Elemental contents (N and P) of eelgrass were variable and demonstrated marked seasonal variations, while the isotope content (δ13C and δ15N) demonstrated marked spatial variations. Elemental contents (N and P) in eelgrass tissues showed a clear annual trend with minima in summer and maxima in spring-winter in Swan Lake. Mean N contents (%) of leaf blades and leaf sheaths in Swan Lake were 2.56 ± 0.89 and 2.53 ± 0.96, respectively, and mean P contents of blades and sheaths were 0.31 ± 0.13 and 0.41 ± 0.17, respectively. N and P contents were higher in aboveground than in belowground tissues; due to C stability, C/N and C/P were lower in aboveground than in belowground tissues. Among different eelgrass populations, the ranges of δ15N isotope ratios in leaf blades and leaf sheaths were 5.57–9.64 and 5.89–9.79, respectively. Elemental (N and P) and isotope (δ13C and δ15N) contents of leaf sheaths were positively correlated with those of blades; this was evident regardless of the season and site, suggesting that the sheath elemental and stable isotope content could be a valuable indicator of that in leaf blades for seagrass ecosystem geochemical research.